Tailored nutrition strategies for Paralympic athletes: addressing unique energy, nutrients, and hydration needs to enhance performance and health - Ghazzawi, Hadeel; Al Aqaili, Raghad; Khataybeh, Batool; Al-Aittan, Fajer; Hamaideh, Saja; Alhalaiqah, Tamara; Amawi, Adam; Trabelsi, Khaled; Jahrami, Haitham; Hasan, Mahmoud AlHaj (Frontiers in Nutrition, 2025)
The achievements of Olympic athletes are often highlighted, whereas the successes of Paralympians are frequently overlooked. Paralympic athletes with disabilities face unique nutritional challenges due to variations in energy expenditure and nutrient requirements associated with their specific disabilities and sports. Hydration is critical, particularly for athletes with spinal cord injuries, who may struggle with body temperature regulation. Despite the importance of nutrition in enhancing athletic performance, there is a lack of research focused on the nutritional requirements of Paralympic athletes. This scholarly review provides a comprehensive overview of the energy, macronutrient, and micronutrient requirements, including those for minerals and vitamins, supplements, and fluid intake, of Paralympic athletes aged 18 and older. This literature search was conducted via the Scopus and Google Scholar databases and focused on English-language original articles published between 1990 and 2024. This review included 56 studies. These findings highlight the necessity for tailored nutritional planning to support the performance and health of Paralympic athletes. Close monitoring of individual intake is essential to adjust for fluctuations in macronutrients, micronutrient supplements, and fluid intake. Ongoing research is vital for developing effective nutritional strategies that accommodate the diverse needs of these athletes.